UPAYA DAN KENDALA MENGATASI TINDAK PIDANA ILEGAL LOGGING DIKAWASAN HUTAN LINDUNG SISIMENI SANAM PADA KECAMATAN AMABI OEFETO - Martha Riberu; Jimmy Pello; Bhisa Vitus Wilhelmus (Petitum Law Journal, 2026)
Research in the Sisimeni Sanam Protected Forest Area in Amabi Oefeto identified systematic factors that cause illegal logging: (1) Economic (community poverty, low choice of other jobs, and demand for illegal wood); (2) Political and Policy (weak law enforcement, corruption among officials, unclear policies, and the involvement of several members of the Indonesian National Armed Forces as perpetrators); (3) Social and Cultural (lack of environmental awareness, local traditions, and low community participation); (4) Geographic and Technical (remote location and low monitoring technology). This study used an empirical legal research method with a qualitative approach to explore these issues in depth. Actions to address these problems (preventive efforts such as socialization and reforestation; repressive efforts such as patrols and sanctions) have proven ineffective due to a number of obstacles: inadequate socialization, weak coordination between institutions, unclear forest area boundaries, complicated licensing processes, and structural obstacles such as corruption and protection of influential individuals. Effective solutions require a comprehensive approach: overhauling forestry policies, eliminating corruption, developing sustainable economies, improving technical capabilities (such as the use of drones or satellites), fair law enforcement (including by law enforcement), and increasing community engagement through environmental education.